The Effectiveness of the Discovery Learning Model on the Quality of Islamic Cultural History Learning - Daldiri, Daldiri; Susanto, Solihin; Haryanah, Rina; Thoyyar, Husni (Fakultas Tarbiyah - Universitas Nahdlatul Ulama Sunan Giri, 2024)
Learning the history of Islamic culture can train students to think chronologically and foster nationalism in planning the future based on past experiences. This research aims to test the effectiveness of the discovery learning model in improving the quality of Islamic Cultural History (SKI) learning and determine learning models that can produce quality SKI learning. The research uses a quantitative approach with a quasi-experimental method, involving an experimental class that applies the discovery learning model and a control class that uses the conventional lecture method. Data sources were taken from the pretest and post-test in both classes. The research was conducted at Madrasah Aliyah Ibadul Ghofur with a sample of class 10 MIA 1 students as the experimental class and class 10 MIA 2 as the control class. The research showed that the discovery learning model effectively improved the quality of SKI learning, with the average post-test score for the experimental class (86.91) being higher than the control class (72.50). The N-gain score measurement shows that the experimental class is in the practical category (70.49), while the control class is ineffective category (35.10). This research concludes that the discovery learning model has also been proven to increase student activity and motivation in learning compared to conventional methods. In conclusion, there is a significant difference in the quality of SKI learning between the control and experimental classes, where the discovery learning method is more effective in improving the quality of learning.